Is language in vocational education and training preparation really the warp and the woof? A German perspective - Peitz, Nina-Madeleine [Verfasser] (My University, 2018)
“German language competence levels are far too low within the group of young adults during their vocational training phases having implications both on their professional future but also on personal success in life. Training Preparation in the German Vocational Education system prepares students on their way from school to work being faced with their increasing diverse backgrounds with respect to mother language and German language abilities. Professional teachers must deal with the challenge of linguistic diversity during subject lessons. Students' language deficiencies lead to barriers of understanding on both sides. The project “Inclusive Qualification Modules (QBI)” connects to these challenges as it develops, tests and evaluates qualification modules in four German vocational schools. Considering the project´s major aim of inclusion and integration, results emphasize the significant role language competence plays and furthermore teachers´ awareness for language in this special target group. Activities of analysis, development, implementation and evaluation are connected in a circular design-based research process. The paper focuses on the final step of the project – the critical analysis and evaluation of the implementation phase of the design with the aim of establishing future theories regarding the design principles in the four case studies. Systematic results are based on group interviews with teachers, curricular analysis, students' questionnaires or students' documents.” (excerpt; BIBB-Doku)
Keywords: S 1.2 Berufsvorbereitung; 370; Berufsausbildungsvorbereitung; Berufsschule; Qualifizierungsbaustein; Sprachkompetenz; Spracherwerb; Evaluation